How to switch from a poor PEDOT:X oxygen evolution reaction (OER) to a good one. A study on dual redox reversible PEDOT:metallacarborane. Issue 30 (19th July 2022) - Maria Xavier, Jewel Ann; Fuentes, Isabel; Nuez-Martínez, Miquel; Kelemen, Zsolt; Andrio, Andreu; Viñas, Clara; Compañ, Vicente; Teixidor, Francesc
Abstract : Here, we dope an electroactive reversible redox polymer PEDOT with a reversible redox active metallacarborane having tunable potential to generate a synergistic material with superior properties such as a low overpotential to generate O2 from water. Abstract : Over the years, extensive research has been carried out to optimize the oxygen evolution reaction (OER) by adopting different techniques as well as catalysts. Conducting organic polymers such as PEDOT have been employed to study the reaction but have failed to lower the over-potential for the reaction. Here we show electrochemically made, intimately blended, dual redox reversible materials incorporating PEDOT and metallacarboranes. The metallacarboranes act as doping agents but with tunable E 1/2 potentials. The tunability of E 1/2 allows the overlapping of the two redox potentials which subsequently leads to their synergy. The physico-chemical properties of the metallacarboranes fade and become integrated with PEDOT to form a dual redox reversible system. Therefore, the properties of the dopant are modified by the polymer. Thus, due to its high E 1/2, the Co 4+/3+ couple would not be an efficient electrocatalyst for water oxidation but when it is immersed in the PEDOT matrix the Co 4+/3+ potential is more accessible so that very low overpotential values are obtained, which justifies the title of the work, How to switch from a poor PEDOT:X oxygen evolution reaction (OER) to a good one . The dual redox reversible system has been extensively characterized and has been shown to be a promising candidate for the water oxidation reaction.